Persepsi Masyarakat dan Tantangan Konservasi Ikan Mola-Mola: Kajian Literatur dan Media Sosial - Pontoiyo, Fuad; Hamidun, Marini Susanti; Dunggio, Iswan; Baderan, Dewi Wahyuni K.; Rahim, Sukirman (JAGO TOLIS : Jurnal Agrokompleks Tolis, 2025)
The mola-mola fish (Mola spp.), or ocean sunfish, is the largest bony fish species in the world, playing a crucial role in marine ecosystems and holding high economic value as an underwater tourism attraction. However, this species faces various threats, such as bycatch, marine pollution, and climate change, which affect its distribution and reproduction. This study aims to analyze public perceptions of mola-mola conservation through a review of literature and social media data. The study involved an analysis of scientific literature using VOSviewer and the collection of social media data, particularly on TikTok, using a web scraper. Sentiment analysis was performed using a machine learning method based on Support Vector Machine (SVM). The results indicate that public perception is dominated by positive sentiment (45%) regarding the unique appeal of mola-mola, although negative sentiment (30%) persists due to a lack of public knowledge about the importance of conservation. This study highlights the need for sustainable habitat management and community-based collaboration to increase conservation awareness. The findings emphasize that public education and collaboration between the government, scientists, and local communities are essential to reduce threats to mola-mola, including the impacts of climate change and illegal fishing. This research underscores that community-based strategies and multidisciplinary approaches can enhance the effectiveness of mola-mola conservation and ensure the sustainability of marine ecosystems in Indonesia.